(untitled) (MMIT Proceedings, 2026)
The paper examines the need to develop a comprehensive regulatory mechanism for crypto-assets in the context of decentralized digital financial systems. The relevance of the study is determined by the fact that traditional regulatory approaches, based mainly on formal restrictions, licensing, and control of individual market participants, do not fully eliminate legal uncertainty in the crypto-asset market. The purpose of the paper is to substantiate a mechanism-oriented model of crypto-asset regulation that integrates declaration, recordkeeping, monitoring, control, enforcement, and regulated circulation into a unified governance system. The study is based on an institutional approach and applies structural-functional, comparative, and mechanism-based analysis. The findings show that the effectiveness of crypto-asset regulation depends not only on the existence of legal norms, but also on the coherence of regulatory procedures, infrastructure intermediaries, financial monitoring mechanisms, and behavioral incentives for market participants. The paper concludes that reducing legal uncertainty requires the development of institutional infrastructure, including banking integration, licensed intermediaries, payment channels, identification procedures, and agency-based access mechanisms to the regulated segment of the crypto-asset market.